Geomechanical evaluation of a middle Cambrian unconventional oil and gas play in the southern Georgina Basin, northern Australia. Issue 5 (4th July 2021) - Tenthorey, E.; Ayling, B.
Abstract: Middle Cambrian sediments in the southern Georgina Basin contain multiple organic-rich source rocks and have been suggested to be prospective for both conventional and unconventional hydrocarbons. We present new geomechanical data collected from the middle Cambrian Arthur Creek Formation and Thorntonia Limestone in four wells (Baldwin 1, MacIntyre 1, Owen 2, Todd 1) in the southern Georgia Basin, and compare the data to mineralogical and geochemical datasets. Geomechanical test intervals were selected to allow geomechanical test results to be directly compared with the mineralogical and geochemical datasets (X-Ray Diffraction, HyLogger and organic geochemistry). Approximately 25 m of core was tested for unconfined compressive strength (UCS) using the scratch-testing technique, and results indicate values in the range of 60–150 MPa. Triaxial testing was also conducted to measure the poroelastic properties of core, and results indicated that Young's modulus is generally in the range of 45–67 GPa. UCS and Young's modulus are positively correlated and increase with depth through the prospective Arthur Creek Formation. The mechanical properties of the tested core are relatively indurated and stiff compared with young sedimentary rocks and broadly similar to proven shale gas plays in Australia and internationally. Mineralogically, the Georgina Basin rocks tested have lower clay contents than rocks from other Australian and international basins but no clear correlation was observed between geomechanical properties and mineralogy, suggesting that multiple factors contribute to the poroelastic and strength parameters. For example, parameters such as sonic velocity and porosity are weakly correlated to rock strength. Geomechanical data can be used alongside other datasets (e.g. sedimentological, geophysical and structural data) to better inform predictions of hydrocarbon prospectivity. KEY POINTS: Middle Cambrian rocks from the Georgina Basin, Australia are prospective for conventional and unconventional hydrocarbons. Rock mechanical tests are conducted to determine how the organic-rich sediments might respond to stimulation. Mechanical analyses are evaluated alongside mineralogical, geochemical and well-log data to assess controls on rock strength properties. Geomechanical behaviour is complex and appears to be driven by multiple factors.